Sosialisasi dan Simulasi Mitigasi Bencana dan Pertolongan Pertama pada Gen-Z di Kota Jayapura - Mujadi, Mujadi; Tammubua, Milcha Handayani; Suratni, Suratni; Rivaldhy, Rivaldhy; Monika, Restu (Abdimas Indonesian Journal, 2024)
Natural disasters cannot be avoided. The provision that can be given is to provide training to all elements of society so that they have the ability to be able to face natural disasters. disaster mitigation and first aid that was held was to increase public awareness about the risk of natural disasters, increase public knowledge in dealing with disasters and increase knowledge about examples of disaster response simulations. The urgency of this activity is to equip generation Z (Gen-Z) in responding to disaster conditions. The partner in this activity is Basarnas with training participants are the community, students and students. Knowledge and techniques to save themselves and victims of natural disasters are important points for Gen-z to remain socialised and not always dependent on technology.